Inhibition of angiogenetic macrophages reduces disc degeneration-associated pain - Hou, Yang; Shi, Jiangang; Guo, Yongfei; Shi, Guodong (Frontiers in Bioengineering and Biotechnology, 2022)
Abnormal angiogenesis and innervation in avascular discs during lumbar disc degeneration (LDD) cause severe back pain. These pathological alterations in the degenerating discs are induced by cytokines partially produced and secreted by inflammatory cells, among which macrophages are the most frequently ones detected at the legion site. However, the role of macrophages as well as their polarization in regulation of innervation and angiogenesis in the degenerating discs is unclear. In this study, we analyzed macrophages in the degenerating discs from patients and detected a specific macrophage subtype that expresses high levels of vascular endothelial growth factor A (VEGF-A). Co-expression of M2 macrophage markers in this macrophage subtype suggested that they were a M2d-like subtype. High levels of VEGF-A and genes associated with angiogenesis were also detected in LDD specimens compared to control heathy discs from a public database, consistent with our finding. Moreover, the levels of VEGF-A in disc macrophages were strongly correlated to the pain score of the examined patients, but not to the Thompson classification of the degeneration level of the patients. In vitro, overexpressing VEGF-A in macrophages increased the tube formation, proliferation and migration of co-cultured endothelial cells, and increased the innervation of embryonic spinal cord explant into the co-cultured area for macrophages and skeletal myocytes. In vivo, an orthotopic injection of adeno-associated virus carrying siRNA for VEGF-A under a macrophage-specific CD68 promoter significantly reduced the number of VEGF-A-positive disc macrophages and alleviated the pain in LDD-mice. Together, these data suggest that inhibition of angiogenetic potential of macrophages may reduce disc degeneration-associated pain through suppression of angiogenesis and innervation, as a promising therapy for LDD-associated pain.